TRANSLATION IN DIFFERENT REGISTER TEXT: A CONTEMPORARY AND PEDAGOGICAL PERSPECTIVE - Dewi , Ni Putu Ayu Kartika Sari; Septiana, Kadek Ayu Kartika; Pratama, Ngurah Artha Yoga; Wulantari, Ni Putu; Suamba, I Made (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the integration of register variation in translation pedagogy, emphasizing the relevance of multimodal awareness and context-based teaching approaches. Register, which is defined through the components of field, tenor, and mode, plays a crucial role in shaping meaning and guiding translators’ decisions across different genres and text types. The growing diversity of contemporary texts, ranging from academic articles to informal digital content, requires translation students to adapt their linguistic and stylistic strategies according to communicative purpose and audience expectations. This study employs a qualitative literature review to examine recent developments in translation theory and instructional practice, highlighting the need for a more adaptive and responsive teaching framework. It proposes a pedagogical model that includes genre-sensitive translation tasks, multimodal translation projects, comparative analysis of texts with different registers, and reflective commentary as instructional tools to enhance translation competence. These strategies help students develop not only linguistic accuracy but also critical awareness of cultural context, appropriate tone, and functional meaning. The findings support the conclusion that effective translation instruction must extend beyond literal meaning, encouraging learners to approach texts with both contextual sensitivity and practical awareness. This research contributes to the development of a register-focused and practice-oriented model for translator education.